2000
DOI: 10.1210/mend.14.8.0497
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Intracellular Movement and Nucleocytoplasmic Recycling of the Ligand-Activated Androgen Receptor in Living Cells

Abstract: An expression construct containing the cDNA encoding a modified aequorea green fluorescent protein (GFP) ligated to the 5'-end of the rat androgen receptor (AR) cDNA (GFP-AR) was used to study the intracellular dynamics of the receptor movement in living cells. In three different cell lines, ie. PC3, HeLa, and COS1, unliganded GFP-AR was seen mostly in the cytoplasm and rapidly (within 15-60 min) moved to the nuclear compartment after androgen treatment. Upon androgen withdrawal, the labeled AR migrated back t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
108
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(122 citation statements)
references
References 54 publications
13
108
1
Order By: Relevance
“…This suggests that the mechanism involved in the inhibition of the AR is functioning within the nucleus. The partial nuclear translocation of the AR we observed is in contrast to a complete nuclear translocation previously reported by immunofluorescence studies in LNCaP cells (Tyagi et al, 2000). The reason for this difference is not clear but is most likely to be explained by the use of different techniques.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…This suggests that the mechanism involved in the inhibition of the AR is functioning within the nucleus. The partial nuclear translocation of the AR we observed is in contrast to a complete nuclear translocation previously reported by immunofluorescence studies in LNCaP cells (Tyagi et al, 2000). The reason for this difference is not clear but is most likely to be explained by the use of different techniques.…”
Section: Discussioncontrasting
confidence: 98%
“…However, in conjunction with the etoposide-induced reduction of DHT bound in the ligand-binding assay, it can be speculated that the ligand binding of the AR is more unstable in the presence of etoposide, which could lead to a dissociation of the ligand from the AR after the nuclear translocation. It has been reported that AR is translocated to the nucleus within an hour of hormone stimulation, but when the ligand is washed off the cells, it takes 12 h for the AR to be relocalised to the cytoplasm (Tyagi et al, 2000). It is therefore possible that in the presence of etoposide, an equilibrium of ligand-bound and -unbound AR is found in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, intracellular localization of AR has been shown to be mediated by sequences located close to, or within the LBD (Zhou et al, 1994;Tyagi et al, 2000;Tomura et al, 2001). The lack of transcriptional repression by unliganded PLZF-AR may be due to its exclusion from the nucleus.…”
Section: Plzf-ar Inhibits the Expression Of An Androgenregulated Repomentioning
confidence: 99%
“…Ligand binding to AR initiates release from the cytoplasm, dimerization, binding to the androgen response elements (ARE) of target genes, and gene activation through interaction with coactivators and the general transcription machinery (2). Functional AREs, consensus sequence 5Ј-GGTACAnnnTGTTCT-3Ј (Fig.…”
mentioning
confidence: 99%